2019
DOI: 10.1142/s0218625x18501780
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphite Additives in Electrolytes on Characteristics of Micro-Arc Oxidation Coatings on 7e04 Aluminum Alloy

Abstract: Micro-arc oxidation coatings were fabricated on 7E04 aluminum alloy substrates by micro-arc oxidation (MAO) in the electrolytes with the graphite addition varying from 0 to 8[Formula: see text]g/L (0, 2, 4, 6, 8[Formula: see text]g/L). The effect of graphite concentration on the surface morphologies, micro-hardness, thickness, phase composition and corrosion resistance of coatings was investigated. With the graphite powder concentration increasing, the oxidation voltage decreased gradually and the thickness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Micro-arc oxidation grows an oxidized ceramic film in situ on the surface of valve metals, via an electrochemical process, including zirconium, titanium, magnesium and their alloys, so as to ameliorate the corrosion resistance, wearability and high-temperature oxidation resistance of the matrix metal [8,9]. The main factors that affect the properties of the MAO coating are electrical parameters [10,11], electrolyte [12] and additives [13]. Among them, additives are regarded as a key factor.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-arc oxidation grows an oxidized ceramic film in situ on the surface of valve metals, via an electrochemical process, including zirconium, titanium, magnesium and their alloys, so as to ameliorate the corrosion resistance, wearability and high-temperature oxidation resistance of the matrix metal [8,9]. The main factors that affect the properties of the MAO coating are electrical parameters [10,11], electrolyte [12] and additives [13]. Among them, additives are regarded as a key factor.…”
Section: Introductionmentioning
confidence: 99%
“…However, heavy metal ions used in electroplating and chemical conversion are environmental pollutants, and the processes are complicated [8]. PEO technology, a new surface technology that is economical and environmentally benign, has been widely studied and applied for its ability to easily generate corrosion-resistant ceramic coatings based on substrate oxides on nonferrous metals surface in situ , such as magnesium, aluminium and titanium [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…At present, PEO coatings are mainly modified by adding different substances to the electrolyte to reduce discharge micro-pores’ size in the coating, increase its thickness, and reduce its porosity [1118]. PEO was used to improve the high corrosion rate of Mg. Wang [19] added appropriate SiC nano-particles to silicate electrolytes to promote cremation discharge and coating growth of magnesium alloy. Li [20] found that adding an appropriate amount of Al 2 O 3 particles to an aluminate electrolyte reduced the content of MgO in the coating and improved the density and corrosion resistance of AM60B magnesium alloy PEO coatings.…”
Section: Introductionmentioning
confidence: 99%